AN ANALYSIS ON THE UTILIZATION OF CHATGPT IN ENHANCING STUDENTS’ ENGLISH LANGUAGE KNOWLEDGE FOR THESIS WRITING: A CASE STUDY OF TWO BEST GRADUATES - Aulia Firdausyiah; Muhammad Yunus (Premise: Journal of English Education and Applied Linguistics, 2026)
The rapid development of artificial intelligence technology has encouraged the use of ChatGPT in academic contexts, particularly in students’ thesis writing processes. This study aims to analyze the utilization of ChatGPT in improving students’ English language knowledge during thesis writing through a case study of two high-achieving graduates. This study employed a qualitative research design using a case study approach. The participants were two best graduates from the English Department who had completed their undergraduate theses and actively used ChatGPT during the writing process. Data were collected through in-depth semi-structured interviews, documentation of thesis drafts and final manuscripts, and indirect observation of writing outputs. The data were analyzed using the interactive model proposed by Miles and Huberman, which consists of data reduction, data display, and conclusion drawing and verification. The findings indicate that ChatGPT was utilized as a supportive tool in writing English abstracts, correcting grammar, constructing academic sentences, and selecting appropriate academic vocabulary. The use of ChatGPT contributed positively to the improvement of students’ English language knowledge, particularly in vocabulary mastery, sentence structure, and grammatical accuracy. These findings suggest that ChatGPT functions as a learning assistant that supports independent learning and enhances students’ academic writing quality, provided that it is used critically and in accordance with academic ethics